The orphan GPR50 receptor promotes constitutive TGFβ receptor signaling and protects against cancer development - Stefanie Wojciech (Nature Portfolio, 2018)
Transforming growth factor-β (TGFβ) regulates many cellular processes. Here the authors show that the orphan G-protein coupled receptor GPR50 can activate the TGFβ receptor I, in the absence of TGFβ, by stabilizing its active conformation and show antitumor activity in a mouse model of breast cancer.